Correction: Correction: Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu Qian; Yang Liang; Shu Linjun Xie; Xiangyu Zhou; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie (Molecular Biology Reports, 2026)

Correction: Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie; Xiangyu Zhou (Molecular Biology Reports, 2026)

Geochronology and Geochemistry of Cretaceous volcanic rocks in the Central Lhasa Block, China: Constraints on the evolution of the Neo-Tethys Ocean - Zhi-Qiang Kang; Rui Wang; Chun-Xi Shan; Ji-Feng Xu; Feng Yang; Sheng-Liang Pei; Ji-Zhong Mu; Ling-Ling Wu; Lu Zhou (Journal of Asian Earth Sciences, 2026)

Decoding lipid signatures and aroma characteristics of four Chinese traditional dark teas via integrative lipidomics, volatilomics, and quantitative descriptive analysis - Shan Zhang; Ruizhi Tang; Yunxia Wang; Ying Wang; Chuang Zhou; Rui Shen; Rui Liang; Niuniu Mao; Yinzi Chen; Nan Deng; Qinghua Zhou; Jia Li; et al. (Food Research International, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Study on upper bound solution of anti-overturning bearing capacity of pile-bucket composite foundation in sand - Guang-si Chen; Rui Zhou; Le Wang; Run Liu; Tian-liang Li (Marine Georesources & Geotechnology, 2026)

Green manuring outperforms cattle manure in soil carbon sequestration by reshaping dissolved organic matter composition and fungal life strategies - Siwei Shi; Songjuan Gao; Guopeng Zhou; Danna Chang; Rui Liu; Ting Liang; Jiudong Zhang; Zongxian Che; Weidong Cao (Soil and Tillage Research, 2026)

Identification and stress-induced expression of Drosomycin and Termicin genes in Shelfordella lateralis - Tie-Long Xu; Rui Zhu; Zu-Liang Li; Cao Zhou (Journal of Asia-Pacific Entomology, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Zr/Al surface enrichment boosts structural stability and electrochemical properties of ultra-high nickel cathode materials - Liang Luo; Jie Chen; Zhongyuan Luo; Rui Zhou; Yuanyuan Chen; Xinyu Zhao; Xianshu Wang; Shunyi Yang; Yingjie Zhang; Yannan Zhang; Kaomin Zhang; Peng Dong; et al. (Chemical Engineering Journal, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Composite beeswax-glycerol monolaurate oleogelation enhances encapsulation efficiency and oxidative stability of microencapsulated Antarctic krill oil - Xin Sun; Liang Song; Rui-Ying Wang; Xin-Yang Ha; Fa-Wen Yin; Lei Qin; Bei-Wei Zhu; Da-Yong Zhou (Food Research International, 2026)

Strip deep rotary tillage reduces the optimal nitrogen rate for high maize yield in the North China Plain: A system-specific optimization of root-shoot growth and soil nitrogen availability - Zhuohan Gao; Hongliang Lan; Zhigang Wang; Xinbing Wang; Zaisong Ding; Rui Wang; Lu Liang; Congfeng Li; Ming Zhao; Baoyuan Zhou (Field Crops Research, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Establishment and comprehensive performance evaluation of auto- and allo-tetraploids derived from Crassostrea gigas and C. angulata - Xianchao Bai; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Rui Xu; Qi Li (Aquaculture International, 2026)

Montmorillonite and solid-phase humic acid differentially regulate mineral transformation and electron flux in dissimilatory iron reduction - Jing Ding; Rui Zhu; Sijia Zhou; Can Yin; Yawen Wang; Liang Li (Journal of Environmental Chemical Engineering, 2026)

Position dependent elasticity of the anterior talofibular ligament in healthy young women: an in-vivo shear wave elastography study - Zili Chen; Wan Zhou; Hao Liang; Xing Liu; Yibo Li; Li Yang; Huijuan Xiang; Rui Du (European Journal of Applied Physiology, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

SB216763 enhances proliferation and sustains the undifferentiated state of porcine spermatogonial cells in prolonged In vitro culture - Benliang Zhou; Zhen Zhang; Anqin Duan; Jiaxiang Ji; Mengqi Li; Rui Chen; Xiangxing Zhu; Jianghua Shang; Xiaogan Yang; Xingwei Liang (Theriogenology, 2026)

Using ethylene combined with green manuring to enhance rice productivity, economic benefit, and energy efficiency in double-rice paddy field - Jinxin Sun; Guopeng Zhou; Danna Chang; Rui Liu; Han Liu; Zhengbo Ma; Ting Liang; Jia Liu; Chunqin Zou; Weidong Cao (Field Crops Research, 2026)

Binasal occlusion modulates cortical functional connectivity and hemodynamics in acquired paralytic esotropia: a fNIRS study - Jie Zhou; Ran Du; Xue Wang; Jun Wu; Fubiao Huang; Rui Fang; Yixiong Liang; Ning Song; Wenbin Wei (Experimental Brain Research, 2026)

SIRT1-regulated mitophagy mitigates lipotoxicity-induced ferroptosis in diabetic kidney disease - Yingchun Jian; Yongqin Zeng; Zhengdi Wang; Xingyan Zhou; Haiping Zhang; Dan Liang; Rui Yan (Apoptosis, 2026)

High breeding potential for growth exists in normal, black, and golden shell lines of tetraploid Fujian oyster revealed through three generations of mass selection - Yuanxin Liang; Qi Li; Xianchao Bai; Geng Cheng; Jianmin Zhou; Rui Xu; Fanzhi Chu; Zhiyang Cui; Chengxun Xu; Wenshu Luo (Aquaculture, 2026)

Depleting SfCarE: Innovative strategies for enhancing chlorantraniliprole toxicity through mixing with carbaryl in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Qinqin Wang; Lin Zhou; Li Wang; Xiangshuai Li; Pei Liang; Changhui Rui; Huizhu Yuan; Li Cui (Pesticide Biochemistry and Physiology, 2026)

Transformation behaviors of polybrominated diphenyl ethers (PBDEs) in electronic waste during thermal dismantling processes: Effect mechanisms of coexisting metals - Jiahao Liang; Jianmin Zhou; Songhan Zeng; Xiaodong Du; He Liu; Yuqing Li; Rui Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Genomic evidence resolves species identity and hybridization in farmed Golden pompano (Trachinotus anak) - Liang Guo; Siqing Wang; Jiehong Wei; Rui Peng; Zhongyuan Shen; Luojing Zhou; Jiaxuan Kang; Ke Rao; Yang Yang; Zhennian Chen; Chang Wu (Aquaculture, 2026)

Novel green ternary deep eutectic solvents for efficient extraction of nitrogen compounds from oil - Yingying Zuo; Rui Zhou; Xiaohang Yang; Jian Wang; Xu Liu; Yushan Li; Zhengqi Liang; Boxing An; Fengjuan Niu (Journal of Environmental Chemical Engineering, 2026)

Hydration-driven structural engineering via enzymatic glycation: Sustained quercetin release in pullulan-zein coatings for extended walnut preservation - Zi-han Wang; Xue-li Liu; Rui-qi Sun; Bin Qi; Jun-xia Xia; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2026)

A comprehensive strategy for solving Cd risk while improving soil quality and rice yield in paddy fields: Co-utilizing green manure, rice straw, and biochar - Ting Liang; Danna Chang; Guopeng Zhou; Cheng Cai; Rui Liu; Jinxin Sun; Songjuan Gao; Zhengbo Ma; Jiancheng Xie; Siwei Shi; Jun Nie; Yulin Liao; et al. (Journal of Hazardous Materials, 2025)

Synergistic lattice engineering and surface passivation via cerium modification for robust ultrahigh-nickel layered oxide cathodes - Lunhao Deng; Rui Zhou; Jie Chen; Xiaotian Xu; Yuanyuan Chen; Xinyu Zhao; Liang Luo; Wang Xiang; Xiangwan Lai; Yingjie Zhang; Xianshu Wang; Ding Wang; et al. (Chemical Engineering Journal, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Multifunctional Au(I)-based AIEgens for the visualization and treatment of invasive fungal infections - Jiawei Zhou; Yizhi Fan; Yajuan Guan; Yiliang Qin; Dawei Liang; Shuangling Deng; Kaihui Shi; Yongyu Rui; Lei Zheng; Jing Zhang (Chemical Engineering Journal, 2025)

SPH–FEM Numerical Simulation of Empty-Hole Cut Blasting in Rock Masses - Xiaorui Cao; Rui Liang; Wenhai Zhou; Xiaoming Lou; Caizhi Hu; Fangxia QI; Xiaowei Chen (Geotechnical and Geological Engineering, 2025)

Dynamic cellular composition and immune landscape revealed by single-cell transcriptome profiling in a brain arteriovenous malformation - Yutong Liu; Hongchuan Niu; Junze Zhang; Rui Liang; Zhenyu Zhou; Chengxu Lei; Shihao He; Changyu Lu; Yuanli Zhao (Functional & Integrative Genomics, 2025)

Melichumarin A, a new coumarin with nitric oxide inhibitory activity from the stems of Melicope chunii - Rui-Hong Zhu; Zi-Feng Liang; Zhong-Liu Zhou; Zi-Ming Chen; Qi Zhou; Jing-Ling Ren; Shou-Yuan Wu (Natural Product Research, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Insights into the key odorants in Chimonanthus praecox var. concolor Mak. Flower using the sensomics approach - Peng Guo; Wei Guan; Runhu Xin; Yuanhao Zhou; Miao Liang; Yajian Wu; Rui Wang; Yuping Liu (Food Chemistry, 2025)

Ternary eutectic solvents facilitate the production of well-dispersed chitin-glucan nanofibrils from shiitake mushrooms - Rui Zhou; Xingyu Yi; Yi Qin; Ruoyun Wu; Yang Wang; Liang Liu; Yimin Fan (Carbohydrate Polymers, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

Heterogeneous dominant factors of heat resilience across diverse urban patterns - Lihao Yao; Rui Zhang; Jiaquan Wu; Weiqiang Zhou; Zixin Liang (Land Use Policy, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Analysis on Phase Polarity of Mandrel Fiber-Optic Vector Hydrophones Based on Phase Generated Carrier Technique - Yatao Li; Jianfei Wang; Rui Liang; Jingjing Feng; Mo Chen; Jiaze Zhao; Zhou Meng (Journal of Marine Science and Engineering, 2025)
In ocean engineering, the demand for fiber-optic vector hydrophones (FOVHs) is increasing. The performance of a FOVH depends on phase consistency between its pressure and acceleration channels, which should match the acoustic field’s properties. Phase polarity, which refers to the alignment of the output signal with the acoustic field direction, is critical. Incorrect phase polarity during sensor assembly can disrupt phase consistency and invalidate directional measurements. This study investigates phase polarity in mandrel FOVHs that use the Phase Generated Carrier (PGC) technique. We develop a theoretical model combining the PGC algorithm with elastic mechanics to analyze the response of acoustic signals. Our model shows that correct demodulated signal polarity requires a specific physical setup: the pressure sensor’s long arm should be on the inner mandrel and the short arm on the outer, while the accelerometer’s positive axis should follow the vector from the long to its short arm. These results are validated through standing wave tube experiments and lake tests. This research provides practical guidelines for the installation and calibration of FOVHs, ensuring phase consistency in underwater acoustic sensing.

Bioactivity of essential oils extracted from four varieties of Zanthoxylum bungeanum against insects and dominant spoilage fungi in Codonopsis pilosulae - Rui Feng; Zhenjia Ma; Jiali Bai; Jie Fan; Chunyu HE; Junlong Wang; Ji Zhang; Junyu Liang; Feng Zhou (South African Journal of Botany, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Improvement of nutritional value of cotton residue by solid state fermentation - Duoting Wu; Xiurong Liang; Rui Hu; Zhisheng Wang; Huawei Zou; Fali Wu; Hui Li; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Hongbo Li; Zhenyong Zhou (Journal of Environmental Chemical Engineering, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Fracture Damage Analysis of Rock Near Blastholes in High-Slope Throw Blasting - Fangxia Qi; Wenhai Zhou; Juan Bao; Xiaoming Lou; Caizhi Hu; Rui Liang (Geotechnical and Geological Engineering, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Co@Al2O3/C3N4 micro-nano catalysts with photothermal confinement effect for enhanced full-spectrum-solar-light-driven CO2 conversion - Yanan Wang; Qi Yin; Rui Zhang; Jie Ma; Song Xu; Qian Liang; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Inhibiting fatty acid-binding protein 4 reverses inflammation and apoptosis in wasp sting-induced acute kidney injury - Ling Li; Hai Yuan; Haoran Li; Rui Cheng; Zilin Zhou; Fengqi Hu; Liang Xu (Food and Chemical Toxicology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Deep Learning-Based Surrogate-Assisted Intelligent Optimization Framework for Reservoir Production Schemes - Lian Wang; Hehua Wang; Liehui Zhang; Liang Zhang; Rui Deng; Bing Xu; Xing Zhao; Chunxiang Zhou; Li Fan; Xindong Lv; Junda Wu (Natural Resources Research, 2025)

Analysis of the Relationship Between Organic Acid, Total Soluble Solids, Total Phenolic, and Total Flavonoids in Ficus carica - Jiajie Luo; Xueqian Dong; Jing Liang; Ming Jia; Lei Sun; Yanling Han; Siduo Zhou; Rui Sun (Applied Fruit Science, 2025)

Climate change impacts on city-scale building energy performance based on GIS-informed urban building energy modelling - Meng Wang; Jingfeng Zhou; Yujing Liang; Hang Yu; Rui Jing (Sustainable Cities and Society, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Ethylene stimulates methane oxidation and inhibits methane production in green manure-rice systems - Jinxin Sun; Zhengbo Ma; Guopeng Zhou; Ting Liang; Rui Liu; Danna Chang; Han Liu; Jia Liu; Chunqin Zou; Weidong Cao (Journal of Environmental Management, 2025)

Facile isolating of chitin nanofibril from silkworm chrysalis and its potential application in structuring oil - Rui Zhou; Xinxia Li; Liang Liu; Yimin Fan (Food Hydrocolloids, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Green Manure Coupled With Straw Returning Increases Soil Organic Carbon via Decreased Priming Effect and Enhanced Microbial Carbon Pump - Guopeng Zhou; Guilong Li; Hai Liang; Rui Liu; Zhengbo Ma; Songjuan Gao; Danna Chang; Jia Liu; David R. Chadwick; Davey L. Jones; Weidong Cao (Global Change Biology, 2025)
Green manuring and crop straw returning are widely used to increase soil organic carbon (SOC) sequestration, while the pathways and drivers in native SOC mineralization and new SOC formation after implementing these practices remain unclear. Here, through a 10‐locations' network field experiment in southern China, the effects of green manuring (Mv), rice straw returning (Rs), and their combination (MR) on soil C sequestration efficiency (CSE) were evaluated. A microcosmic experiment was performed to trace the components and participants of SOC mineralization and formation under the three practices. The network experiment showed that Mv, Rs, and MR annually improved SOC stock by 119.7, 477.0, and 830.2 kg C ha −1 , respectively, with MR having the highest CSE of 23.1%, followed by Rs (17.7%) and Mv (13.3%). The microcosmic experiment further revealed that the highest CSE in MR most likely resulted from the low mineralization of native SOC (positive priming effects, PE) and great formation of new SOC through microbial C pump (MCP). Therein, MR mainly downregulated the K‐strategists of the microbial community (e.g., Gaiellales ) to yield negative PE on recalcitrant native SOC, such as protein/amino sugar‐ and lignin‐like molecules; meanwhile, MR had the highest bacterial and fungal MCPs, which were, respectively, led by r‐strategists (e.g., Sporobacter ) and molds (e.g., Cladosporium ). The study highlights the advantages of mixing low‐ (Rs) and high‐quality (Mv) residues for efficiently increasing SOC sequestration and firstly discovers the core microbes that dominate the mineralization and formation of SOC in paddy fields.

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Strategic regulation of crystallization kinetics to achieve efficient pure-red quasi-2D perovskite light-emitting diodes - Yunhui Kuang; Yazhuo Xue; Zheng Zhang; Lvpeng Yang; Tong Bie; Rui Li; Wenxi Liang; Naigen Zhou; Ming Shao (Chemical Engineering Journal, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Equol promotes the in vitro maturation of porcine oocytes by activating the NRF2/KEAP1 signaling pathway - Sai Xiao; Ke Peng; Rui Chen; Xinxin Liu; Benliang Zhou; Rijing He; Yujun Yan; Runtian Wan; Ye-Shi Yin; Shengsheng Lu; Xingwei Liang (Theriogenology, 2025)

Efficient photothermal conversion and Z-scheme charge transfer in narrow-gap semiconductor heterojunction for photothermal-assisted photocatalysis - Yu-Ting Chen; Wen-Xi Xia; Yuan Zhou; Qi-Rui Zhang; Xiang-Bai Chen; Liang Ma; Si-Jing Ding (Journal of Environmental Chemical Engineering, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

In vivo quantification of polyphosphate in Microcystis aeruginosa using DAPI staining - Rui Zhu; Xiao Tan; Zhipeng Duan; Yijia Wei; Imran Ali; Jiang Huang; Jia Liang; Jianyong Hu; Jiazhi Zhang; Zixin Zhou (Algal Research, 2025)

Natural and anthropogenic forcing of ecological and environmental changes at Lake Qilu, SW China, since the last deglaciation - Kaiyu Cao; Lin Chen; Yongxiu Lu; Yao Zhang; Mengjing Li; Duo Wu; Yilong Wang; Liang Chen; Xiaonan Zhang; Rui Yang; Youliang Huang; Aifeng Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Controllable construction of ratiometric fluorescent probe based on Ag/Au nanoclusters and silicon nanoparticles for multivariate detection of Ag+, Cu2+, and Hg2+ - Jingyu Pang; Linan Zhou; Zhuang Liang; Tingting Li; Rui Yan; Fang Chai (Journal of Environmental Chemical Engineering, 2024)

Frictional contact-vibration coupling model for tbm rock cutting with multi-cutter - Meng-qi Zhang; Rui-xue Sun; Ji-liang Mo; Zhong-rong Zhou (Computers and Geotechnics, 2024)

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

Ignoring the food route underestimated human health risk from potentially toxic elements in agricultural environments of Ziyang, Shaanxi, China - Hao Wu; Jingyi Shi; Rongxin Ren; Jing Du; Fei Zhou; Mingxing Qi; Wanchen Zhao; Xiaoping Du; Zengrun Xia; Rui Ren; Dongli Liang (Environmental Geochemistry and Health, 2024)

A novel inactivated oral rabies vaccine with the incorporation of U-OMP19 enhances the immunogenicity by reducing viral proteins degradation and activating dendritic cells in a mouse model - Zonghui Zeng; Di Wu; Jingyi Xiong; Jianqing Zhao; Chuan Liang; Qiong Wu; Chengli Huang; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Green manuring combined with zeolite reduced nitrous oxide emissions in maize field by targeting microbial nitrogen transformations - Rui Liu; Danna Chang; Guopeng Zhou; Hao Liang; Jiudong Zhang; Qiang Chai; Weidong Cao (Science of The Total Environment, 2024)

A granular thermodynamic constitutive model considering THMC coupling effect for hydrate-bearing sediment - Rui Zhou; Bing Bai; Liang Chen; Yongchen Zong; Nan Wu (Ocean Engineering, 2024)

Olfactory perceptual interactions of maltol with key food odorants in binary mixtures: Scatter matrix statistical analysis of odor intensity in heterogeneous perceptual situation - Wei Guan; Runhu Xin; Miao Liang; Yuanhao Zhou; Rui Wang; Yuping Liu (Food Chemistry, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Co-incorporation of wheat straw and hairy vetch reduced soil N2O emission via regulating nitrifier and denitrifier structure on the Qinghai plateau - Rui Liu; Peng Jiang; Guopeng Zhou; Danna Chang; Hao Liang; Qiang Chai; Weidong Cao (Applied Soil Ecology, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Cu-II-directed self-assembly of fullerenols to ameliorate copper stress in maize seedlings - Chenjie Fan; Qingyuan Liang; Yan Wang; Peimei Chen; Jiakai Wu; Qingnan Wu; Shijun Jiang; Yang Zhou; Rui He; Fuju Tai (Science of The Total Environment, 2024)

Feasibility of sulfated BPA and BPS as wastewater-based epidemiology biomarkers: Insights from wastewater and reported human urine analysis - Hao Wang; Rui Gao; Weiqian Liang; Yingyue Zhou; Zhuo Wang; Longxia Lan; Jinfeng Chen; Feng Zeng (Science of The Total Environment, 2024)

Revolutionizing sustainable economic growth in China: Harnessing natural resources, green development, and fintech for a greener future. - Liang Chen; Rui Ma; Jing Li; Fengjiao Zhou (Resources Policy, 2024)

Assessment and management for future habitat risks under the implementation of China's territorial spatial planning: A case study from Hainan Island - Xiaolin Zhang; Xiaobin Jin; Xinyuan Liang; Xu Shi; Rui Sun; Wenjie Zhu; Jinhuang Lin; Bo Han; Yinkang Zhou (Environmental Impact Assessment Review, 2024)

Brain-Derived Exosomal CircRNAs in Plasma Serve as Diagnostic Biomarkers for Acute Ischemic Stroke - Xinli Jiang; Rui Zhang; Geng Lu; Yu Zhou; Jianfeng Li; Xinrui Jiang; Shuangshuang Gu; Hongwei Liang; Jun Wang (Journal of Neuroimmune Pharmacology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Modeling nitrogen removal performance based on novel microbial activity indicators in WWTP by machine learning and biological interpretation - Yadan Yu; Hao Zeng; Liyun Wang; Rui Wang; Houzhen Zhou; Liang Zhong; Jun Zeng; Yangwu Chen; Zhouliang Tan (Journal of Environmental Management, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

PHLDA1 is a P53 target gene involved in P53-mediated cell apoptosis - Xuhong Song; Lulu Zhou; Wenrui Yang; Xinyan Li; Jiazi Ma; Kun Qi; Rui Liang; Meijing Li; Lingzhu Xie; Tin Su; Dongyang Huang; Bin Liang (Molecular and Cellular Biochemistry, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

One pot synthesis of hydrophobic nanochitin aerogel via tert-butyl alcohol/water binary solvents as antibacterial and renewable oil superabsorbent - Liang Liu; Xinxia Li; Rui Zhou; Yimin Fan (Carbohydrate Polymers, 2024)

AM fungus promotes wheat grain filling via improving rhizospheric water & nutrient availability under drought and low density - Hai-Xia Duan; Chong-Liang Luo; Rui Zhou; Ling Zhao; Shuang-Guo Zhu; Yinglong Chen; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Microbial mechanism of biochar addition to reduce N2O emissions from soilless substrate systems - Xiaofeng Liang; Wanlai Zhou; Rui Yang; Dongdong Zhang; Hong Wang; Qiaozhen Li; Zhiyong Qi; Yuzhong Li; Wei Lin (Journal of Environmental Management, 2023)

Exploring the relation between aggregation and adsorption of microplastics in aquatic environment containing metal cations - Weiqian Liang; Yingyue Zhou; Shuyin Wei; Longxia Lan; Jinfeng Chen; Jiawei Zhao; Hao Wang; Rui Gao; Feng Zeng (Journal of Environmental Chemical Engineering, 2023)

Three Types of Enteromorpha prolifera Bio-Products Based on Different Processing Procedures as Feed Additives in the Diets of Pacific White Shrimp (Litopenaeus vannamei) - Zhibin Zhou; Lubo Wang; Mingqin Dai; Qingyan Gao; Peng Wang; Lili Zhao; Yanlu Li; Rui Xi; Mingchao Pan; Qiang Ma; Houguo Xu; Mengqing Liang; et al. (Fishes, 2023)
A feeding trial was conducted to evaluate the biological activities of Enteromorpha prolifera bio-products in the diets of Pacific white shrimp (Litopenaeus vannamei). Bio-products of E. prolifera included E. prolifera meal, E. prolifera hydrolysate and E. prolifera polysaccharide, which was supplied using different processing procedures. The control diet was supplemented without any E. prolifera bio-products or dietary attractants. Experimental diets were formulated to contain 0.2% and 0.4% of E. prolifera hydrolysate (EPH0.2% and EPH0.4%), 0.03% of E. prolifera polysaccharide (EPP0.03%), 3% of E. prolifera meal (EPM3%), 0.1% of dimethyl-β-propiothetn (DMPT0.1%) and 1% of squid paste (SP1%). Shrimp (~8 g) were randomly distributed in 21 tanks and fed for 44 days. Feed intake showed that 3% of E. prolifera meal and 0.4% of E. prolifera hydrolysate in diets exhibited similar attractant effects as 0.1% of DMPT. Gross qualitative observation showed that the abundance of lipid droplets decreased in hepatopancreas of the EPH0.4% and EPM3% groups, which were supported by hepatopancreas triacylglycerol (TG), where significantly lower concentrations were observed in the EPH0.4% and EPM3% groups compared with the control group. Similarly, TG and low-density lipoprotein cholesterol in serum significantly decreased in the EPH0.4%, EPP0.03% and EPM3% groups compared to the control group. Supplemental E. prolifera bio-products resulted in significantly higher serum glutathione level of EPP0.03% or superoxide dismutase activities of EPH0.4% and EPM3%, but significantly lower serum malondialdehyde level of EPM3%. In addition, tnf-α expression in hepatopancreas was significantly down-regulated in shrimp fed the EPH0.2%, EPH0.4% and EPM3% diets. Based on survival analysis, E. prolifera bio-products improved the resistance of shrimp to hypoxic stresses. Thus, this study confirmed that bio-products of E. prolifera supplied using different processing procedures could be used to reduce the amount of E. prolifera in feed of shrimp without compromising their biological functions.

Integrative risk assessment method via combining geostatistical analysis, random forest, and receptor models for potentially toxic elements in selenium-rich soil - Hao Wu; Nan Cheng; Ping Chen; Fei Zhou; Yao Fan; Mingxing Qi; Jingyi Shi; Zhimin Zhang; Rui Ren; Cheng Wang; Dongli Liang (Environmental Pollution, 2023)

Gravity-driven membrane system treating heavy metals-containing secondary effluent: Improved removal of heavy metals and mechanism - Xiaobin Ma; Yanrui Wang; Le Tong; Jiaoying Luo; Rui Chen; Yuanxin Wang; Xishou Guo; Jinlong Wang; Zhiwei Zhou; Jingyao Qi; Guibai Li; Heng Liang; et al. (Chemosphere, 2023)

Large-scale biomonitoring of bisphenol analogues and their metabolites in human urine from Guangzhou, China: Implications for health risk assessment - Hao Wang; Rui Gao; Weiqian Liang; Shuyin Wei; Yingyue Zhou; Zhuo Wang; Longxia Lan; Jinfeng Chen; Feng Zeng (Chemosphere, 2023)

Hybrid force-displacement-based design methods for self-centering wall structures - Ying Zhou; Xinwen Liang; Yiqiu Lu; Rui Wang (Soil Dynamics and Earthquake Engineering, 2023)

The effect of stabilized culture of Lactobacillus rhamnosus GCC-3 on gut and liver health, and anti-viral immunity of zebrafish - Hui Liang; Yadong Xie; Ming Li; Jie Chen; Wenhao Zhou; Rui Xia; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Uncertainty in China's food self-sufficiency: A dynamic system assessment - Xinyuan Liang; Xiaobin Jin; Xiaoxiao Xu; Hefeng Chen; Jing Liu; Xuhong Yang; Weiyi Xu; Rui Sun; Bo Han; Yinkang Zhou (Sustainable Production and Consumption, 2023)

Understanding land-use sustainability with a systematical framework: An evaluation case of China - Bo Han; Xiaobin Jin; Rui Sun; Hanbing Li; Xinyuan Liang; Yinkang Zhou (Land Use Policy, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

Molecularly imprinted polymers embedded with double perovskite quantum dots: A ratiometric fluorescence sensor for visible and fluorescent determination of Rhein - Rongkun Zhu; Zengcheng Du; Mingfang Zhu; Huanru Liang; Shumei Wang; Qing Zhou; Rui Li; Yulan Li; Chaoying Zeng; Wenhao Liu; Qiqing Chen (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A corrected p-y curve model for large-diameter pile foundation of offshore wind turbine - Xiao-ling Zhang; Rui Zhou; Guo-liang Zhang; Yan Han (Ocean Engineering, 2023)

Biomimetic chitosan nanoparticles with simultaneous water lubricant and anti-inflammatory - Lumin Yang; Haofei Huang; Huajing Zeng; Xiaoduo Zhao; Rui Wang; Zhengfeng Ma; Zengjie Fan; Yong-min Liang; Shuanhong Ma; Feng Zhou (Carbohydrate Polymers, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

A New Framework Based on Data-Based Mechanistic Model and Forgetting Mechanism for Flood Forecast - Guozhen Wei; Wei Ding; Guohua Liang; Bin He; Jian Wu; Rui Zhang; Huicheng Zhou (Water Resources Management, 2022)

Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie; Xiangyu Zhou (Molecular Biology Reports, 2022)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Detoxification difference of cadmium between the application of selenate and selenite in native cadmium-contaminated soil - Mingxing Qi; Yang Liu; Yanan Li; Min Wang; Nana Liu; Pornpimol Kleawsampanjai; Fei Zhou; Hui Zhai; Mengke Wang; Quang Toan Dinh; Rui Ren; Dongli Liang (Environmental Science and Pollution Research, 2021)

Heterogeneity of tight sandstone reservoirs based on fractal theory: the Xu-6 member of Xujiahe Formation in Guang'an area, central Sichuan Basin - Fang Shen; Liang Yue; Ziliang Liu; Wei Yang; Kaarel Mänd; Hui Jin; Fengjie Li; Yue Zhou; Minghe Zhang; Rui Jiang (Arabian Journal of Geosciences, 2021)

Microseismicity-based method for the dynamic estimation of the potential rockburst scale during tunnel excavation - Guo-Feng Liu; Quan Jiang; Guang-Liang Feng; Dong-Fang Chen; Bing-Rui Chen; Zhou-Neng Zhao (Bulletin of Engineering Geology and the Environment, 2021)

Co-incorporating leguminous green manure and rice straw drives the synergistic release of carbon and nitrogen, increases hydrolase activities, and changes the composition of main microbial groups - Guopeng Zhou; Danna Chang; Songjuan Gao; Ting Liang; Rui Liu; Weidong Cao (Biology and Fertility of Soils, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Impact of policy incentives on electric vehicles development: a system dynamics-based evolutionary game theoretical analysis - Xiao Zhou; Rui Zhao; Liang Cheng; Xuefeng Min (Clean Technologies and Environmental Policy, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Temperature-control-induced masculinization in tiger puffer Takifugu rubripes - He Zhou; Zixin Zhuang; Rui Zhang; Qizheng Xu; Yuting Liang; Zhiqiang Jiang; Xia Li; Tianyu Ma; Yajuan Li (Journal of Oceanology and Limnology, 2019)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Effects of fine particle content and sample scale on the failure properties of loose landslide deposits - Bin-rui Gan; Xing-guo Yang; Ming-liang Chen; Jia-wen Zhou (Arabian Journal of Geosciences, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Three new polyketides from the marine sponge-derived fungus Trichoderma sp. SCSIO41004 - Xiaoyan Pang; Xiuping Lin; Yongqi Tian; Rui Liang; Junfeng Wang; Bin Yang; Xuefeng Zhou; Kumaravel Kaliyaperumal; Xiaowei Luo; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2018)

Attenuation of ethanol abstinence-induced anxiety- and depressive-like behavior by the phosphodiesterase-4 inhibitor rolipram in rodents - Mei-Fang Gong; Rui-Ting Wen; Ying Xu; Jian-Chun Pan; Ning Fei; Yan-Meng Zhou; Jiang-Ping Xu; Jian-Hui Liang; Han-Ting Zhang (Psychopharmacology, 2017)

Warming Effects on Ecosystem Carbon Fluxes Are Modulated by Plant Functional Types - Ji Chen; Yiqi Luo; Jianyang Xia; Kevin R. Wilcox; Junji Cao; Xuhui Zhou; Lifen Jiang; Shuli Niu; Katerina Y. Estera; Rujin Huang; Feng Wu; Tafeng Hu; et al. (Ecosystems, 2017)

Assessing the vulnerability of changing coasts, Hainan Island, China - Yaping Wang; Benwei Shi; Liang Zhang; Jianjun Jia; Xiaomin Xia; Liang Zhou; Rui Yu; Yang Yang; Jianhua Gao (Acta Oceanologica Sinica, 2017)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

piggyBac transposon-derived targeting shRNA interference against the Bombyx mori nucleopolyhedrovirus (BmNPV) - Fang Zhou; Rui-ting Chen; Yan Lu; Shuang Liang; Mei-xian Wang; Yun-gen Miao (Molecular Biology Reports, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells - Hao-Liang Ke; Ying-Wen Zhang; Bi-Fa Zhou; Rui-Tang Zhen (Natural Product Research, 2012)

Characterization of a spliced variant of human IRF-3 promoter and its regulation by the transcription factor Sp1 - Wei Ren; Liang-Hua Zhu; Hua-Guo Xu; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Multiple amino acid variations in the nonstructural proteins of swine Japanese encephalitis virus alter its virulence in mice - Rui Wu; Yongxiang Tian; Junhua Deng; Keli Yang; Wangwang Liang; Rui Guo; Zhengying Duan; Zewen Liu; Danna Zhou; Diping Xu (Archives of Virology, 2011)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)

The Genetic Diversity Among Leymus Species Based on Random Amplified Microsatellite Polymorphism (RAMP) - Rui-Wu Yang; Yong-Hong Zhou; Ying Zhang; You-Liang Zheng; Chun-Bang Ding (Genetic Resources and Crop Evolution, 2006)

Biophysical studies of a ruthenium(II) polypyridyl complex binding to DNA and RNA prove that nucleic acid structure has significant effects on binding behaviors - Hong Xu; Yi Liang; Peng Zhang; Fen Du; Bing-Rui Zhou; Jun Wu; Jian-Hong Liu; Zhi-Gang Liu; Liang-Nian Ji (JBIC Journal of Biological Inorganic Chemistry, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)